Pequena coleção de obras não realizadas: obras imaginadas, projetos e instruções - Ariel Ferreira Costa (2009)
The text leads itself to the composition of a Short Collection of Non-Accomplished Works (Pequena Coleção de Obras Não Realizadas); an imaginary collection which could contribute for the critical understanding of non-accomplished works of art. The objects of this Collection will shape analysis of cases. The artistic neovanguards from the middle of the 20th century and the contemporary art will be historically related. The North American conceptualist art will be partially approached; the exhibition Do Corpo à Terra (1970); works made under Cildo Meireles and Yoko Onos instructions; and non-accomplished projects by the artists: Rubens Mano, Dora Garcia, Narda Alvarado and Carlos Garaicoa.